Health hazard allowance for Nursing professionals: A reflective analysis under the principle of human dignity - Rita de Cassia Ezaias; Maria Helena Palucci Marziale; Jair Aparecido Cardoso
Objective: to discuss the classification of the health hazard allowance due to exposure to biological agents attributed to Nursing professionals, based on legal and occupational parameters supported on the principle of human dignity. Method: an original reflection study with theoretical analysis on legislation, jurisprudence and Occupational Health focused on the biological risks, health hazard and rights of Brazilian workers. The discussions were based on the current legislation and on scientific evidence. Results: the classification of the health hazard allowance due to exposure to biological agents attributed to Nursing professionals is not in line with the factual situation experienced by them. Conclusion: it becomes necessary to broaden the discussion on the subject matter and to review the effective and fair compensation of Nursing professionals due to exposure to potentially contaminated biological agents in their work environments, given that the health hazard allowance is a worker's right and is based on human dignity.